A Phylogeny-Informed Analysis of the Global Coral-Symbiodiniaceae Interaction Network Reveals that Traits Correlated with Thermal Bleaching Are Specific to Symbiont Transmission Mode - Timothy D. Swain (American Society for Microbiology, 2021)
Recent advances have revealed a complex network of interactions between coral and Symbiodiniaceae. Specifically, nonrandom association patterns, which are determined in part by restrictions imposed by symbiont transmission mode, increase the sensitivity of the overall network to thermal stress.